Pendampingan Motivasi bagi Tenaga Kesehatan di Rumah Sakit Umum Daerah Kabupaten Karawang berbasis Webinar - Solehudin; Ibtihal Qomariyyah Luthfiyyah; Sulaeman, Eman; Sri Rahayu (Universitas Muhammadiyah Surakarta, 2023)
In the Covid-19 pandemic situation, everyone can feel they are in a crisis position, including health workers who take care of Covid-19 patients in hospitals so they need support. The purpose of implementing this service is to provide support, strengthening, and assistance in the implementation of handling Covid-19 patients at Karawang Hospital. Increase morale, loyalty, and performance of health workers. The implementation method used is (1) lecture and (2) brainstorming. The results obtained after carrying out assistance through this webinar, 90% of health workers feel happy to be cared for by the campus community. Their loyalty is guaranteed to be very, very good, it can be seen that 100% no one wants to resign. Awareness of self-performance management has increased, it can be seen that 92,7% of them feel reminded by this webinar, that personal performance documentation should not be neglected even though the Covid-19 pandemic situation. Lectures that emphasize calm and optimism, and ensure that the Covid-19 pandemic situation is certain has passed, have a significant impact on the morale, loyalty, and performance of health workers. The brainstorming which combines the stories and feelings of the health workers at the Karawang Hospital has ensured that we really empathize with them (health workers), so they no longer experience mental fatigue.